Spindle cell carcinoma of the gingiva: A rare occurrence - Anjana Ramamurti; Madhumathi Venkataraman; Malathi Narasimhan; Suresh Ranga Rao (Wolters Kluwer Medknow Publications, 2013)
Of the many neoplasms known, squamous cell carcinoma (SCC) is the most common to affect the oral cavity. Spindle cell carcinoma (SpCC) is considered a rare high malignant variant of SCC occurring predominantly in the upper aerodigestive tract. Soft-tissue spindle cell neoplasms are quite uncommon in the oral cavity reportedly accounting for lesser than 1% of all tumors in the oral region. Our case shows an unusual presentation of SpCC involving the mandibular gingiva in a 46-year-old smoker patient, which presented as a firm, erythematous swelling with surface necrosis. An incisional biopsy was performed for microscopic evaluation to confirm the clinical diagnosis and for treatment planning.